PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN DISIPLIN TERHADAP KEPUASAN KERJA DI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN PENAJAM PASER UTARA - Saputro, Argo; Hadiyatno, Didik; Cahyaning Putri, rah (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The purpose of this study was to determine the effect of leadership, communication, and discipline on job satisfaction at the office of the Regional Disaster Management Agency of North Penajam Paser Regency. The type of research used is quantitative research. The sampling technique in this study used purposive sampling with a population of 74 employees, so the sample taken in this study at the office of the Regional Disaster Management Agency of North Penajam Paser Regency amounted to 46 employees who would be used as a research sample size. The data collection method was carried out by distributing questionnaires. This study uses multiple linear regression with the help of SmartPLS in processing data. The results of this study indicate that the leadership variable affects job satisfaction at the North Penajam Paser Regency Regional Disaster Management Agency office, the training variable affects job satisfaction at the North Penajam Paser Regency Regional Disaster Management Agency office, and the discipline variable affects job satisfaction at the North Penajam Paser Regency Regional Disaster Management Agency office.